In-depth exploration of the energy utilization and pyrolysis mechanism of advanced continuous microwave pyrolysis. (15th June 2021) - Luo, Juan; Sun, Shichang; Chen, Xing; Lin, Junhao; Ma, Rui; Zhang, Rui; Fang, Lin
Graphical abstract: Highlights: The comparisons between continuous and batch microwave pyrolysis are analyzed. Continuous microwave pyrolysis can elevate the yield and heating value of biofuels. Continuous microwave pyrolysis has low energy consumption and high energy efficiency. The pyrolysis mechanism of continuous microwave pyrolysis is preliminarily explored. Abstract: Continuous microwave pyrolysis, an advanced method that can realize continuous large-scale feeding under high temperature, has the potential to improve the yield and quality of biofuels, which can address the limits of batch microwave pyrolysis of low efficiencies of resources and energy. However, the energy conversion and pyrolysis mechanisms of continuous microwave pyrolysis remain poorly understood, which may be a key to its highly efficient industrial application. This work addresses this issue by comparing the distribution, compositions, and quality of biofuels obtained by two pyrolysis technologies and then the energy efficiency is analyzed in detail. Thus, the energy conversion mechanism and pyrolysis mechanism of continuous microwave pyrolysis was explored via in-depth study of batch microwave pyrolysis in previous studies. The results demonstrate that continuous microwave pyrolysis offers advantages in terms of the increased yields and quality of biofuels. The maximum biofuels yield of continuous microwave pyrolysis was 72.16% and the maximum lower heating value of bio-gas and bio-oil was 19.50 MJ/Nm 3 and 25.58 MJ/Kg, respectively. Moreover, continuous microwave pyrolysis significantly improved energy efficiency of the process under extended continuous operation, which reached a maximum of 18.47%. The improved performance of continuous microwave pyrolysis is due to continuous high-temperature instantaneous feeding coupling with the conveying and stirring functions of auger increase of the mass transfer and heat transfer between the feedstock and pyrolysis products. This work provides an appropriate process option and theoretical basis of continuous microwave pyrolysis for developing the industrial production of high-grade biofuels from wastes.